Analysis of learning impact of MBKM Plunturan Wiradesa Program for partners and Universitas 17 Agustus 1945 Surabaya - Puspaningtyas, Anggraeny; Masruchin, Febby Rahmatullah; Halik, Abdul (Technium Social Sciences Journal, 2022)
The Wiradesa activity which was held in Plunturan Village, Ponorogo Regency provided a new learning experience for students in implementing the current MBKM curriculum. Direct learning in the field with partners to implement the knowledge that has been obtained when learning on campus, as well as new knowledge gained in the field enrich learning activities for students. The involvement of the State Administration Study Program Wiradesa Program brought by the Student Executive Board (BEM) FISIP was held in Plunturan Village, Pulung District, Ponorogo Regency. Where the business specifications are existing MSMEs and pioneering MSMEs that have been appointed as supporting identities for Plunturan Cultural Tourism Village. Its activity is to develop existing and pioneering businesses. The impact of implementing Wiradesa is not only felt by students, but also for lecturers and partners. Therefore, through this research, the authors conducted a survey to determine the impact of the implementation of Wiradesa activities on learning in the MBKM curriculum for students, lecturers and partners which was carried out in Plunturan Village, Pulung District, Ponorogo Regency. The results of the research carried out are that there is an impact on MBKM learning through Wiradesa activities in Plunturan Village with the resulting benefits greatly impacting the economy, social and other sectors. The impact on universities related to improving the performance of the KPI can be grouped into 3, namely the direct, ongoing and potential impacts. The direct impacts include the 2nd KPI, where students get experience outside of campus and the 7th KPI, which is a collaborative and participatory class. The ongoing impact in the 5th IKU is that the work of lecturers is used by the community. The potential impacts include the 1st KPI, which means that graduates get decent jobs and the 3rd KPI, which is lecturers who are active outside the campus.